Analysis of Steady-State Conditions in 110/35 kV Power Networks with Distributed Generation and Compensating Equipment - Muzaffar B. Khudayarov; Nuriddin N. Normamatov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: distribution power networks, which are predominantly radial (i.e., open-loop) in configuration, have traditionally relied on centralized electricity generation and its delivery from supply centers to end-users. However, in recent years, there has been a significant increase in the deployment of distributed generation based on renewable energy sources such as solar panels and wind turbines. In parallel, the use of compensating devices—such as capacitor banks—has been expanding to regulate voltage, correct power factor, and improve network efficiency by reducing energy losses. The integration of such devices into the network enhances overall efficiency by minimizing transmission losses. However, the introduction of distributed generation elements and compensating devices presents new and complex challenges for analyzing the operation of open-loop distribution networks, compared to traditional passive systems. These new components may cause bidirectional power flows, voltage fluctuations, and current level variations, necessitating a revision and adaptation of conventional load flow calculation methods. Moreover, the variable and difficult-to-predict nature of renewable energy sources (solar, wind, and bioenergy) requires constant adaptation of network operating conditions. Therefore, there is a growing need for modeling and optimizing the operating modes of 110/35 kV power networks under real conditions. This topic is particularly relevant in Uzbekistan, Central Asia, and other developing countries, where strategies for expanding renewable energy infrastructure are being actively pursued. Analyzing the operation of power networks from the standpoint of technical, economic, and environmental efficiency has become an essential demand of the present energy transition. Aim: the main objective of this study is to analyze the steady-state operation and calculate energy losses in 110/35 kV power networks equipped with distributed generation and compensating devices. Methods: in this study, the operating conditions of open-loop 110/35 kV distribution networks were calculated using a two-stage (forward and backward sweep) load flow method, while energy losses were determined using the average load method. Four operating scenarios were considered: without any elements, with only a solar power plant (SPP), with only a reactive power source, and with both components operating together. MATLAB programming environment was used for modeling. In each scenario, node voltages, power flow, and energy losses were analyzed. Results: according to the results, the use of either solar power plants or reactive power sources individually in 110/35 kV networks leads to positive changes in voltage stability. However, the highest efficiency and the lowest energy losses were achieved through the combined use of SPP and reactive power compensation devices.